2021
DOI: 10.21873/invivo.12387
|View full text |Cite
|
Sign up to set email alerts
|

Newly-identified Pathways Relating Vitamin D to Carcinogenesis: A Review

Abstract: Background: The epidemiological relationship between vitamin D levels and cancer has been thoroughly investigated. Published data from large studies appear to corroborate a significant relationship between higher serum vitamin D concentrations and improved survival. Mechanistic reviews on commonly-studied cancers -including breast cancer, colon cancer and melanoma -focus predominantly on data from older studies. In outlining avenues for future research, we believe there is utility in summarizing novel findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…It is well established that 1,25(OH) 2 D 3 exerts its cancerinhibiting activity in many cell types through various direct (e.g., regulation of the cell cycle, induction of apoptosis, inhibition of angiogenesis and tumor-invasiveness,metastasis and -proliferation) and indirect (e.g., regulation of immuno-modulation, effect on tumor microenvironment) mechanisms (95,118). Although AHR-activated CYP1A1 is associated with pro-carcinogen transformation and cancer development, some studies documented a contribution to cancer prevention (27).…”
Section: Relative Mrna Expression Of Cox2 In Hacat and Scl-1 Cells 6 ...mentioning
confidence: 99%
See 3 more Smart Citations
“…It is well established that 1,25(OH) 2 D 3 exerts its cancerinhibiting activity in many cell types through various direct (e.g., regulation of the cell cycle, induction of apoptosis, inhibition of angiogenesis and tumor-invasiveness,metastasis and -proliferation) and indirect (e.g., regulation of immuno-modulation, effect on tumor microenvironment) mechanisms (95,118). Although AHR-activated CYP1A1 is associated with pro-carcinogen transformation and cancer development, some studies documented a contribution to cancer prevention (27).…”
Section: Relative Mrna Expression Of Cox2 In Hacat and Scl-1 Cells 6 ...mentioning
confidence: 99%
“…Notably, it has been shown that 1,25(OH) 2 D 3 modulates the cell cycle through checkpoint regulation (118). Binding to the promoter region of genes encoding p21 and p27 results in cyclin dependent kinase (CDK) inhibition and cell cycle arrest in the G 1 phase via decreased cyclin D1 expression (95,118).…”
Section: Relative Mrna Expression Of Cox2 In Hacat and Scl-1 Cells 6 ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, BC cells have shown higher VDR protein levels compared to benign breast tissue [ 39 ]. Through this transcription factor, calcitriol exerts many anticancer effects, including growth inhibition, induction of cell differentiation, anti-inflammatory activity, cell cycle arrest, oncogenes downregulation, and many others that place calcitriol as a natural endogenous cancer-preventive antineoplastic factor [ 40 , 41 ]. This has been the basis of the vast number of studies designed to study calcitriol and its analogs as pharmacological options in the oncological setting [ 42 ].…”
Section: Calcitriol In Combination With Chemo/radiotherapy In Bcmentioning
confidence: 99%